Color and shading of containers affects root-zone temperatures and growth of nursery plants - Markham, John W. III (Kansas State University, 2010)
Heat stress is an important problem in potted nursery plants, but container color may moderate effects of solar radiation on container soil temperatures. Field studies were conducted near Manhattan, Kansas, USA during summer to evaluate effects of container color on growth of roots and aboveground biomass in: bush beans (Phaseolus vulgaris); red maple (Acer rubrum); and eastern redbud (Cercis canadensis). In the tree studies, effects of shaded soil-surfaces on plant growth were also evaluated. Four treatments among studies included containers colored black (control), flat white, gloss white, and silver, with two additional treatments in the tree studies of green and black containers with shaded soil surfaces (black shaded); treatments were arranged in a completely randomized design. Plants were grown in a bark-based soil-less media, and temperatures were measured at 5 cm depths in the sun-facing sides and centers in five containers per treatment. After four months (June-October), plant variables were measured. Roots were separated into three sections: core (10.2 cm diam.), north, and south, rinsed of all media, dried and weighed. In the bean study, media temperatures at the sun-facing side averaged lowest in gloss and flat white (~36 oC) and greatest in the black control (50.3 oC). Accordingly, total root biomass at the sun-facing side was reduced by 63 to 71% in black compared to flat and gloss white containers. In heat-sensitive maples, media temperatures at the sun-facing side averaged up to 7.7 oC greater in black, black shade and green than in other treatments; temperatures in black shade may have been lower if shade cloth had covered the sun-facing sides of containers in addition to only the media surface. Media temperatures in the core averaged 3.5 to 3.8 oC greater in black than in flat and gloss white, resulting in up to 2.5 times greater belowground biomass and up to 2.3 times greater aboveground biomass in flat and gloss white than in black pots. In heat-tolerant redbuds, the effects of container color on whole-plant growth were less evident. Data suggests that heat-sensitive plants benefit from using white pots or painting outer surfaces of green and black pots white.
Keywords: Heat stress; Nursery plants; Container color; Container temperature; Root zone temperature; Root zone growth; Agriculture, Forestry and Wildlife (0478); Agriculture, General (0473); Agriculture, Plant Culture (0479)